Building global art infrastructure from Nigeria: ART X Lagos and Lagos Biennial 2019“We Are Our Own Sun” - Stacey KENNEDY (E-REA)
The paper argues that developments in art infrastructure on the African continent strengthen African perspectives within the global art ecosystem. Although dichotomies of centre/periphery have been much critiqued, the ascendant contemporary African art market of the last two decades (Enwezor & Okeke-Agulu) continues to be valorised in Euro-American art capitals under hegemonic systems of aesthetic value judgment and critique based on Western positions (Corrigall). Case studies of two institutional interventions, ART X Lagos (art fair) and Lagos Biennial (both 2019), demonstrate a shift in the focus of art narratives and histories to Nigeria and provide examples of a re-shaping of global art infrastructure from the African continent. Based on ethnographic research including participant observation, interviews with curators and artists, as well as interpretations of art venues and artworks, the article intertwines an empirical and theoretical approach grounded in post/decolonial critique, an approach heavily engaged with art and curatorial practice. The article contributes to empirical knowledge about art events in Nigerian spaces and understanding creative contexts on the continent. It concludes that collaborative efforts by Nigerian and African diaspora artists are focused on strengthening Lagos as an art centre — its ‘own sun’ — in a regional and continental art ecosystem. Ultimately this draws the attention of Western art institutions and realigns international circuits of contemporary art towards Nigeria.